Thermal Characterization 2-Methoxybenzoate of Bivalent Metal Ion Complexes - Mahida Mehul Kumar Manaharsinh, Dr. Neelu Jain (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Bivalent ion interaction Studying the reactions of Co (II), Ni (II), Cu (II), and Zn (II) with 4,6-dihydroxy-2-mercaptopyrimidine (DHMP) in the presence of oxalic acid (Ox), malonic acid (Mal), o-phenylene diamine (OPDA), 2,2-bipyridyl (Bipy), 1,10-phenanthroline (phen), and ethylene diamine (En). Compounds of the solid form M-2-MeO-Bz have been synthesised; M denotes the bivalent metals Mn, Co, Ni, Cu, and Zn, while 2-MeO-Bz is 2-methoxybenzoate. Differential scanning calorimetry (DSC), X-ray powder diffractometry, thermogravimetry, and derivative thermogravimetry were all utilised to describe and evaluate the thermal behaviour of these substances.